Severe Diverticulitis Associated to Clostridioides difficile Infection in a 91 Year Old Patient (Clinical Case) - A. A. Makushina; L. N. Androsova; K. B. Puzakov; A. V. Okhlobystin; M. A. Tatarkina; O. S. Shifrin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To present a clinical case of a 91-year-old patient with a severe course of diverticulitis combined with the development of Clostridioides difficile-associated disease.Key points. On admission the patient complained of pain in the left iliac region, increased body temperature, constipation and bloating. The medical history showed that constipation increased on the background of prolonged bed rest and discontinuation of psyllium. According to the laboratory and instrumental examinations, the patient had signs of acute diverticulitis, antibacterial therapy was corrected twice, positive dynamics of the condition was noted. However, a few days later, the patient developed a clinic of C. difficile-associated disease, which required the prescription of anticlostridial therapy (vancomycin), until the laboratory confirmation of the accession of this infection was obtained. Combined therapy of exacerbation of diverticular disease and C. difficile-associated disease made it possible to achieve a steady improvement of the condition.Conclusion. The exclusion of possible development of C. difficile-associated disease on the background or prior antibiotic therapy is an important condition for correct and adequate management of a patient with exacerbation of diverticular disease. If the patient develops a clinical picture of C. difficile-associated disease, treatment may be initiated before laboratory confirmation.